Dwika Lodia Putri, Faizah Kamila Corporate Performance Analysis With Swot Balance Scorecard Method At State Saving Bank (Persero) Tbk Pekanbaru Branch Office - admin admin (Universitas Nias Raya, 2018)
The purpose of this study is to determine the performance of PT. State Savings Bank (Persero) Pekanbaru Branch using SWOT Balance Scorecard approach. Data completion technique used. Data analysis was done by using descriptive analysis.This study looked at 4 (four) perspectives of performance perspective assessment, financial, customer, internal business development, growth and learning.The result of this research is from 4 (four) perspective of performance appraisal, hence obtained average equal to 72,69, result which arises explain PT Bank Tabungan Negara (Persero) Pekanbaru Branch has good performance in category A.